Trade, Diplomacy, and Warfare: The Quest for Elite Rhizobia Inoculant Strains - Checcucci, Alice; DiCenzo, George C.; Bazzicalupo, Marco; Mengoni, Alessio (Frontiers in Microbiology, 2017)
Rhizobia form symbiotic nitrogen-fixing nodules on leguminous plants, which provides an important source of fixed nitrogen input into the soil ecosystem. The improvement of symbiotic nitrogen fixation is one of the main challenges facing agriculture research. Doing so will reduce the usage of chemical nitrogen fertilizer, contributing to the development of sustainable agriculture practices to deal with the increasing global human population. Sociomicrobiological studies of rhizobia have become a model for the study of the evolution of mutualistic interactions. The exploitation of the wide range of social interactions rhizobia establish among themselves, with the soil and root microbiota, and with the host plant, could constitute a great advantage in the development of a new generation of highly effective rhizobial inoculants. Here, we provide a brief overview of the current knowledge on three main aspects of rhizobial interaction: trade of fixed nitrogen with the plant; diplomacy in terms of communication and possible synergistic effects; and warfare, as antagonism and plant control over symbiosis. Then, we propose new areas of investigation and the selection of strains based on the combination of the genetic determinants for the relevant rhizobial symbiotic behavioural phenotypes.